Aflatoxin Effect of Moulded Gala Waste Mixed with Ginger and Its Histopathological Study on Clarias Gariepinus. (Global Journal of Science Frontier Research, 2012)
A feeding trial was conducted to investigate aflatoxin effect of moulded sausage waste with ginger and its histopathological study on Clarias gariepinus. One hundred and eighty fingerlings with mean weight 3.90gÂ±0.02 were stocked at 15fish/net happas (0.8mx0.6mx0.4m).The net happa were suspended into Â¾ of an earthen pond of (12mx12mx1.5m) LXBXH using kuralon twine at the four edges of the happas to tie around carefully arranged bamboo poles across an earthen pond. The fingerlings were fed with four isonitrogenous diets containing 40% crude protein at different inclusion level. Treatment 1 (0% control diet), Treatment 2 (10%), Treatment 3 (20%), and Treatment 4 (30%).The fingerlings were fed at 5% body weight for 8 weeks. It was observed that there was a significant difference (p
Keywords: moulded sausage histopathological study on Clarias gariepinus